PEDIATRIC ENTEROCOLITIS: CLINICAL MANIFESTATIONS AND MANAGEMENT STRATEGIES - Ginel Baciu; Carmen Baciu; Cristina Maria Mihai; Tatiana Chisnoiu; Ramona Mihaela Stoicescu; Adriana Luminita Balasa; Adriana Mocanu; Lorenza Forna; Alexandru Paul Baciu (Romanian Journal of Oral Rehabilitation)
Diarrhea is a leading cause of illness and death in children under five years old. Severe cases of diarrhea, particularly those resulting in dehydration, are a major factor in high mortality rates. Rotavirus is a significant pathogen contributing to dehydrating diarrhea and hospitalizations in children under five. The aim of this study was to investigate the role of vaccination in preventing the progression of gastroenteritis, with a focus on rotavirus-induced gastroenteritis. Material and methods: The present study was conducted within the Pediatric Department of The Emergency Clinical Hospital “St. Apostle Andrew” in Constanța, including 307 patients diagnosed with acute gastroenteritis during the period of January 1 and December 31, 2023. Results: The prevalence declined with age: 183 infants, 67 patients were between 1 and 3 years old, 42 were aged 3 to 7, and the smallest group, 15 patients, were between 7 and 16 years old, and 201 of the 307 children did not receive the Rotarix or Rotateq vaccines, while 106 patients completed the full vaccination regimen. As for the etiology of the disease, 160 patients were diagnosed with acute viral enterocolitis, with 142 cases attributed to Rotavirus. An increase in dehydration and electrolyte imbalances was observed in subjects who had not received the preventive Rotavirus vaccine. Conclusion: The role of the vaccine in preventing the severe progression of gastroenteritis, particularly that caused by Rotavirus, is highlighted by the reduced frequency of dehydration, electrolyte imbalances, and shorter hospital stays in patients who received the Rotarix/Rotateq vaccine.